219k views
14 votes
Solve the systemof linear equations -3x+y=2 -x+y-4=0​

User Shamari
by
5.6k points

1 Answer

11 votes

Answer:

(1, 5)

Explanation:

Substitution works well here. Solving the second equation for x, we get x = y - 4. Substituting y - 4 for x in the first equation results in

-3(y - 4) + y = 2.

Next, we perform the indicated multiplication and obtain:

-3y + 12 + y = 2, or -2y = -10

Dividing both sides by -2 yields y = 5. As seen above, x = y - 4; if y = 5, then x = 5 - 4 = 1.

The solution is (1, 5)

User Mzafer
by
4.7k points